2004
DOI: 10.1191/0267659104pf760oa
|View full text |Cite
|
Sign up to set email alerts
|

Refractory ventricular fibrillation in accidental hypothermia: salvage with cardiopulmonary bypass

Abstract: A 20-year old woman presented with prolonged refractory ventricular fibrillation and pulmonary oedema following hypothermia while she was under self-administered heroin in an attempt to commit suicide. She was successfully resuscitated with cardiopulmonary bypass for core rewarming and internal defibrillation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…In accordance with these findings, hypothermia of 30°C increased the vulnerability to pacing‐induced ventricular fibrillation by facilitating wave breaks and promoting the onset of ADP alternans in Langendorff‐perfused isolated rabbit hearts . The increased incidence of ventricular fibrillation, which is frequently observed in patients suffering from accidental hypothermia, was also experimentally confirmed in vivo in a porcine model …”
Section: Discussionsupporting
confidence: 73%
“…In accordance with these findings, hypothermia of 30°C increased the vulnerability to pacing‐induced ventricular fibrillation by facilitating wave breaks and promoting the onset of ADP alternans in Langendorff‐perfused isolated rabbit hearts . The increased incidence of ventricular fibrillation, which is frequently observed in patients suffering from accidental hypothermia, was also experimentally confirmed in vivo in a porcine model …”
Section: Discussionsupporting
confidence: 73%
“…Air pockets indicated that they had been breathing before HCA ( 66 , 94 , 95 , 100 ). Fifteen men and eight women suffered HCA secondary to drug or alcohol abuse ( 2 , 45 , 46 , 53 , 54 , 56 , 57 , 62 , 63 , 70 , 76 , 81 , 86 , 90 , 91 , 98 , 101 , 104 , 105 , 109 , 121 ). All underwent successful resuscitation with ECLS.…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen case reports were also reviewed [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31], yielding a total of 17 patients. Fourteen of these patients suffered an exposure-related hypothermic arrest, all 14 of these survived neurologically intact.…”
Section: Case Reportsmentioning
confidence: 99%